2012
DOI: 10.4049/jimmunol.1101111
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-Dioxin Induces Transcriptional Activity of the Human Polymorphic hs1,2 Enhancer of the 3′Igh Regulatory Region

Abstract: 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is an environmental toxicant known to inhibit antibody secretion and Ig expression. Inhibition of Ig expression may be partially mediated through repression of the 3’Igh regulatory region (3’IghRR). TCDD inhibits mouse 3’IghRR activation and induces aryl hydrocarbon receptor (AhR) binding to dioxin response elements (DREs) within the 3’IghRR enhancers: hs1,2 and hs4. The human hs1,2 enhancer (hu-hs1,2) is polymorphic due to the presence of one to four invariant sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 66 publications
(119 reference statements)
0
26
0
Order By: Relevance
“…Furthermore, there is a binding site (i.e. dioxin response element, DRE) for the aryl hydrocarbon receptor (AhR), which can be activated by a variety of structurally diverse ligands, including dietary and microbiota-derived ligands [23,30]. Indeed, it is becoming increasingly acknowledged that the AhR is an important environmental sensor and regulator of mucosal immunity and AhR knockout mouse models have demonstrated an essential role of the AhR in the structural integrity of the gut (reviewed by [31]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, there is a binding site (i.e. dioxin response element, DRE) for the aryl hydrocarbon receptor (AhR), which can be activated by a variety of structurally diverse ligands, including dietary and microbiota-derived ligands [23,30]. Indeed, it is becoming increasingly acknowledged that the AhR is an important environmental sensor and regulator of mucosal immunity and AhR knockout mouse models have demonstrated an essential role of the AhR in the structural integrity of the gut (reviewed by [31]).…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from buccal cells using the GenElute Mammalian Genomic DNA Kit following the manufacturer's instructions (Sigma-Aldrich, St. Louis, MO). Nested PCR was completed as previously outlined [17,23]. Briefly, for the first round of PCR, 1 μg of genomic DNA was used as a template to selectively amplify a 5.4 kb fragment of the 3′ IGH RR-1 (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tolerance induction was associated with expansion of CD4 + C-D25 + Foxp3 + Tregs. While TCDD has been shown to inhibit B cell differentiation and antibody production in vitro (91)(92)(93)(94), no studies have yet demonstrated a potential benefit in transplantation. In humans, there is some observational evidence that traffic air pollution may shorten the life of lung transplants through the development of bronchiolitis obliterans syndrome (95).…”
Section: Impact Of Pollutants On Graft Outcomementioning
confidence: 99%